Classification of brain stroke based on susceptibility-weighted imaging using machine learning - Kandaya, Shaarmila; Saad, Norhashimah Mohd; Abdullah, Abdul Rahim; Shair, Ezreen Farina; Muda, Ahmad Sobri; Sabri, Muhammad Izzat Ahmad (Institute of Advanced Engineering and Science, 2025)
Magnetic resonance imaging (MRI) is used to identify brain disorders, particularly strokes. Rapid treatment, often referred to as